2018
DOI: 10.1080/23322039.2018.1518116
|View full text |Cite
|
Sign up to set email alerts
|

The role of FDI inflows and export on economic growth in Sri Lanka: An ARDL approach

Abstract: This paper examines the long-run and short-run relationship between Foreign Direct Investment (FDI) inflows, exports, and economic growth in Sri Lanka over 1980-2016. The study implies Autoregressive Distributed Lag (ARDL) bounds testing approach to reveal the relationship between the variables. The study indicates that FDI inflows have a positive and significant relationship with economic growth in the long-run and short run. If FDI inflows increase, GDP growth will increase. But for exports, it has a negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 48 publications
4
19
0
2
Order By: Relevance
“…These results are an indication that exports and foreign remittances take more time for positive spillover effects on economic growth of India. The study of Pereira and Xu (2000) and Sultanuzzaman et al (2018) also found negative impact of exports on economic growth. Given the trade policy of countries and their composition of exports, it indicates that exports and foreign remittances take more time as compared to imports and FDI for positive spillover effects on economic growth of India.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…These results are an indication that exports and foreign remittances take more time for positive spillover effects on economic growth of India. The study of Pereira and Xu (2000) and Sultanuzzaman et al (2018) also found negative impact of exports on economic growth. Given the trade policy of countries and their composition of exports, it indicates that exports and foreign remittances take more time as compared to imports and FDI for positive spillover effects on economic growth of India.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, ARDL and error correction metric (ECM) have been applied to investigate the relation and causality (if any) between economic growth and other variables in India. Many studies such as Pesaran et al (2001), Pacheco-Lopez (2005), Chaudhary (2006), Zachariadis (2006) and Sultanuzzaman et al (2018) have used ARDL which proved effective to examine dynamic relation between GDP and other related variables. This study attempts to estimate relationship between economic growth, FDI, exports, imports and foreign remittances through ARDL bound estimation both in the short run and long run.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The econometric model used is a heterogeneous dynamic Autoregressive Distributed-lag (ARDL) as suggested Pesaran and Smith (1995); Hashem and Shin (1998); Pesaran et al (1999) and augmented bounds testing, which is used when variables are integrated of different orders (Pesaran, Shin, & Smith, 2001). Also of the most recent studies that have the ARDL is most effective tools and appropriate model to examine dynamic presentation between variable (Goh, Sam, & McNown, 2017;Paramati, Ummalla, & Apergis, 2016;Sultanuzzaman, Fan, Akash, Wang, & Shakij, 2018;Sunde, 2017). Proved Unlike a VAR model that is rigorously for endogenous variables, the ARDL model is fit for the combination of endogenous and exogenous variables.…”
Section: Estimation Techniquementioning
confidence: 99%
“…210-220;Sahoo & Dash, 2012, pp. 217-252;Sultanuzzaman et al, 2018). Here, Sri Lanka's economic ties with China in particular were a key aspect of its explanation.…”
Section: Literature Reviewmentioning
confidence: 99%